Komparasi Nilai Tambah Pengolahan Kopi Arabika UMKM Sumber Wandhe Wonosalam, Jombang - Mufidah, Afifahtul; Ariyani, Aminah Happy Moninthofa (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Raw materials are a crucial aspect of businesses, particulary in coffee processing enterprises. During times of crop failure, farmers experience a lack of harvest, causing limited production capacity. Therefore, value-added analysis is essential to be understood as a consideration for the Sumber Wandhe MSMEs in managing their products to ensure business sustainability and MSME productivity improvement. One type of coffee that processed is arabica coffee in the form of dried coffee beans (green beans). Sumber Wandhe MSME uses four types of processing methods namely natural (dry), natural anaerobic, full washed (wet), and honey. This research aims to comprehend and compare the value-added of arabica coffee processing in each method. The employed analysis method is quantitative descriptive, and the data analysis technique involves calculating the Hayami value-added. The research findings reveal that the highest value-added is found in the anaerobic natural method at Rp.17,776.33/kg with a value-added ratio of 60.60%, whereas the lowest value-added is in the honey method at Rp.12,656.67/kg with a value-added ratio of 52.37%. All arabica coffee processing methods in the Sumber Wandhe MSMEs fall under the category of high value-added ratio, where the value-added is >40%. A recommendation for the Sumber Wandhe MSMEs is to increase the production of arabica coffee using the anaerobic method due to its highest value-added and profitability.